2014
DOI: 10.1159/000363233
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine for Continuous Wound Infusion for Postoperative Pain Management: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: The use of continuous wound infusion (CWI) of local anaesthetics has been suggested as a safe and effective alternative technique to epidural anaesthesia/analgesia that allows surgeons to provide postoperative pain relief while reducing opioid consumption and associated adverse events. A previous meta-analysis by Liu et al. [Am Coll Surg 2006;203:914-932] reported results mainly from studies of bupivacaine. Subsequently, several new randomized controlled trials (RCTs) of ropivacaine have been publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…70 A more recent meta-analysis of 14 RCTs (756 patients) focused on ropivacaine for WCI, the authors noting consistent evidence of effective analgesia and opioid sparing in a wide range of surgical procedures such as total knee or hip replacement, and major abdominal and cardiac surgery. 71 Similarly, a meta-analysis of infiltrative techniques (WCI, TAP, intraperitoneal) versus placebo for routine analgesia for colorectal surgery concluded that the infiltrative techniques were associated with lower pain scores, reduction of opioid requirements, shorter length of stay and no increase in complications. 72 It must be emphasised that all studies with wound infiltration are not positive.…”
Section: Wound Infiltration and Catheter Infusion Techniquessurprisinmentioning
confidence: 99%
“…70 A more recent meta-analysis of 14 RCTs (756 patients) focused on ropivacaine for WCI, the authors noting consistent evidence of effective analgesia and opioid sparing in a wide range of surgical procedures such as total knee or hip replacement, and major abdominal and cardiac surgery. 71 Similarly, a meta-analysis of infiltrative techniques (WCI, TAP, intraperitoneal) versus placebo for routine analgesia for colorectal surgery concluded that the infiltrative techniques were associated with lower pain scores, reduction of opioid requirements, shorter length of stay and no increase in complications. 72 It must be emphasised that all studies with wound infiltration are not positive.…”
Section: Wound Infiltration and Catheter Infusion Techniquessurprisinmentioning
confidence: 99%
“…102 A more recent meta-analysis of 14 RCTs (756 patients) focused on ropivacaine for wound catheter infusion; the authors noted consistent evidence of effective analgesia and opioid sparing across a wide range of surgical procedures including TKA. 103 Plasma concentration of local anesthetic was below toxic levels, despite 8 to 20 mg/h ropivacaine infusion for 48 hours. 103 Wound catheter infusion techniques should preferably be called surgical-site catheter techniques because the catheters are not always strictly in the surgical wound.…”
Section: Wound Catheter Infusion Techniquesmentioning
confidence: 92%
“…103 Plasma concentration of local anesthetic was below toxic levels, despite 8 to 20 mg/h ropivacaine infusion for 48 hours. 103 Wound catheter infusion techniques should preferably be called surgical-site catheter techniques because the catheters are not always strictly in the surgical wound. In clinical practice, catheters have been placed through the surgical wound into deeper layers and in cavities (subcutaneous, subfascial, subacromial, intraarticular, intraperitoneal, preperitoneal, intraosseous, etc).…”
Section: Wound Catheter Infusion Techniquesmentioning
confidence: 92%
“…Ropivacaine is a long‐acting local anesthetic increasingly used in the management of postoperative analgesia. A meta‐analysis has recently presented some evidence of the clinical efficacy of ropivacaine continuous wound infusion (CWI) in a wide range of surgical procedures . This technique is one of the multimodal pain relief strategies used to prevent acute and chronic pain and to reduce opioid consumption and side effects.…”
mentioning
confidence: 99%
“…A meta-analysis has recently presented some evidence of the clinical efficacy of ropivacaine continuous wound infusion (CWI) in a wide range of surgical procedures. 1 This technique is one of the multimodal pain relief strategies used to prevent acute and chronic pain and to reduce opioid consumption and side effects. In women undergoing breast cancer surgery, CWI of ropivacaine is a promising procedure used to prolong the analgesic effect, 2 which could allow an ambulatory setting and early discharge home.…”
mentioning
confidence: 99%